Performance in mathematics in the state of São Paulo in the light of a Gini educational indicator - Capelato, Erika [UNESP]; de Abreu, Jamil Gomes; Corrêa, André Luiz [UNESP] (Revista Meta - Avaliacao, 2023)
In this work we analyze the performance in mathematics of the administrative regions and the metropolitan region of São Paulo. First, we propose an educational indicator to measure school performance. Next, we obtain the value of this indicator using the grade of public high school students in the School Performance Assessment System of the State of São Paulo (Saresp). Finally, using linear regression, we investigated the relationship between math performance and socioeconomic variables. The results showed that the administrative region of São José do Rio Preto presented the best results of the educational indicator and the metropolitan region of São Paulo, the worst results. In addition, we observed that performance in mathematics and economic variables are positively related.
Rendimiento en matemáticas en el estado de São Paulo a la luz de un indicador educativo de Gini
Desempenho em matemática no estado de São Paulo à luz de um indicador educacional do tipo Gini
Keywords: Educational Indicator; Math; SARESP